Evolution of Servitization: new business model opportunities - Aitor Ruiz de la Torre; David Sanchez (International Journal of Production Management and Engineering)
The concept of Servitization has been constantly developing since its outset, but in the last decade due to the irruption of Industry 4.0, the complexity of the concept and its typologies of value propositions have evolved considerably, opening up endless opportunities. In this sense, the main objective of this research is to show a summary review of the evolution of Servitization since its beginnings and the new typologies that are emerging due to the digitalization that arises through Industry 4.0. For this purpose, a systematic review of the leading databases in the field of services has been conducted. The results of the literature review show the potential of Servitization and the need to understand each reality in order to adapt to new capabilities that help the companies who become service-oriented benefit from major advantages. Ultimately, it can be concluded that, in the short term, Industry 4.0 and its new business models are the key, however, Servitization will continue to evolve to a point where all organizations will need to adapt to new trends.